Remote ischemic preconditioning for prevention of high-altitude diseases: fact or fiction? - Berger, Marc Moritz; Macholz, Franziska; Mairbäurl, Heimo; Bärtsch, Peter (Journal of applied physiology, 2015)
Preconditioning refers to exposure to brief episodes of potentially adverse stimuli and protects against injury during subsequent exposures. This was first described in the heart, where episodes of ischemia/reperfusion render the myocardium resistant to subsequent ischemic injury, which is likely caused by reactive oxygen species (ROS) and proinflammatory processes. Protection of the heart was also found when preconditioning was performed in an organ different from the target, which is called remote ischemic preconditioning (RIPC). The mechanisms causing protection seem to include stimulation of nitric oxide (NO) synthase, increase in antioxidant enzymes, and downregulation of proinflammatory cytokines. These pathways are also thought to play a role in high-altitude diseases: high-altitude pulmonary edema (HAPE) is associated with decreased bioavailability of NO and increased generation of ROS, whereas mechanisms causing acute mountain sickness (AMS) and high-altitude cerebral edema (HACE) seem to involve cytotoxic effects by ROS and inflammation. Based on these apparent similarities between ischemic damage and AMS, HACE, and HAPE, it is reasonable to assume that RIPC might be protective and improve altitude tolerance. In studies addressing high-altitude/hypoxia tolerance, RIPC has been shown to decrease pulmonary arterial systolic pressure in normobaric hypoxia (13% O2) and at high altitude (4,342 m). Our own results indicate that RIPC transiently decreases the severity of AMS at 12% O2. Thus preliminary studies show some benefit, but clearly, further experiments to establish the efficacy and potential mechanism of RIPC are needed.